Goalkeeper, characteristics of the position, playing, technique, training - Struzik, A. (Central European Journal of Sport Sciences and Medicine, 2020)
Changes in a goalkeeper`s technique, his physical and mental preparation are ongoing, forced by the increasing power of the throw, speed of the game, improved players` throwing capability; throws with rotation and other technical innovations involved in this element. The goalkeeper`s tasks are not only limited to defending the goal. He participates in launching a quick attack or quickly resuming play after conceding a goal. Goalkeeper training should be varied in order to mobilize the body`s full energy potential and shape the elements of the technique. The goalkeeper should be intelligent, courageous, endowed with the excellent physical condition and above all physically fit.